The Impact Of Motivational Factors And Task-Related Behavior On Employee Performance - Dewiana, Dewiana; Baskara, Ika; Hafidz, Gilang Pratama (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the influence of intrinsic and extrinsic motivation on employee task-related behavior and performance at PT. Admiral Lines. The background of this study is the instability of employee performance, so a study was conducted to determine the dominant motivational factors that influence employee task-related behavior and performance. The population of this study were employees of PT. Admiral Lines, with samples taken using purposive sampling techniques totaling at least 85 respondents. This study used a quantitative method with the Structural Equation Modeling - Partial Least Square (PLS-SEM) approach. The results of the study showed that intrinsic motivation has a positive influence on task-related behavior, but does not have a positive effect on employee performance. Conversely, extrinsic motivation has been shown to have a positive influence on employee task-related behavior and performance. In addition, task-related behavior also plays a significant mediation role in the relationship between motivation (intrinsic and extrinsic) and employee performance. These findings indicate that in order to improve employee performance, companies need to pay attention to motivational factors, especially extrinsic motivation, such as financial rewards and incentives, which have proven effective in influencing employee performance. After conducting the study, the researcher suggested expanding the population to the branches of PT. Admiral Lines which are located in other regions in Indonesia, in order to represent more answers from PT. Admiral Lines employees throughout Indonesia. In addition That way, you can add other supporting variables to measure employee performance such as job satisfaction and employee engagement or other relevant variables as research innovations. Keywords : intrinsic motivation, extrinsic motivation, task-related behavior, employee performance